2013
DOI: 10.1080/00224499.2012.757281
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality Examined Through the Lens of Attachment Theory: Attachment, Caregiving, and Sexual Satisfaction

Abstract: Attachment researchers have proposed that the attachment, caregiving, and sexual behavioral systems are interrelated in adult love relationships (Mikulincer & Shaver, 2007 ). This study examined whether aspects of partners' caregiving (proximity, sensitivity, control, compulsive caregiving) mediated the association between their attachment insecurities (anxiety and avoidance) and each other's sexual satisfaction in two samples of committed couples (Study 1: 126 cohabiting or married couples from the general co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 52 publications
4
50
0
1
Order By: Relevance
“…Other studies have also found notable gender differences pertaining to the link between avoidance and sexual adjustment. For instance, avoidance was related to sexual dissatisfaction in men but not in women in a sample of clinically distressed couples (Brassard et al, 2012), and caregiving control reported by the partner (i.e., support aimed at solving problems for the partner while minimizing opportunities for the partner to solve problems on his/her own, Kunce & Shaver, 1994) predicted higher sexual satisfaction in men, but lower sexual satisfaction in women (Péloquin et al, 2014). This later finding appears to suggest that partner involvement (whether through sensitive or insensitive support) is related to better sexual adjustment in men.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other studies have also found notable gender differences pertaining to the link between avoidance and sexual adjustment. For instance, avoidance was related to sexual dissatisfaction in men but not in women in a sample of clinically distressed couples (Brassard et al, 2012), and caregiving control reported by the partner (i.e., support aimed at solving problems for the partner while minimizing opportunities for the partner to solve problems on his/her own, Kunce & Shaver, 1994) predicted higher sexual satisfaction in men, but lower sexual satisfaction in women (Péloquin et al, 2014). This later finding appears to suggest that partner involvement (whether through sensitive or insensitive support) is related to better sexual adjustment in men.…”
Section: Discussionmentioning
confidence: 96%
“…Individuals high on attachment avoidance tend to dislike or even avoid sexuality altogether (Brassard, Shaver, & Lussier, 2007;Tracy et al, 2003), and tend to prefer uncommitted, emotion-less or solitary sexual activity (Bogaert & Sadava, 2002). Unsurprisingly, both anxiety and avoidance are related to lower sexual satisfaction in community and clinical samples (Butzer & Campbell, 2008;Little, McNulty, & Russell, 2010;Péloquin, Brassard, Lafontaine, & Shaver, 2014), and to poorer sexual functioning, including lower sexual arousal and pleasure, as well as sexual pain (Birnbaum, 2007;Brassard, Dupuy, Bergeron, & Shaver, in press;Granot, Zisman-Ilani, Ram, Goldstick, & Yovell, 2010).…”
Section: Attachment and Sexualitymentioning
confidence: 93%
“…It has been estimated that approximately 15%À20% of marital vitality and satisfaction is attributable to good sexual functioning in the relationship; when sexual behavior becomes problematic, it has a disproportionate impact on relationship satisfaction as it has been reported that sexual problems account for 50%À70% of distress in relationships (McCarthy, 2003;Woolley, 2006). P eloquin, Brassard, Delisle, andB edard (2013) reported evidence that engaging in sexual intercourse was associated with both attachment style and current caregiving pattern, thus expanding the scope of attachment to include the attachment relationship with a specific intimate partner, and demonstrating that attachment may be a critical factor in understanding dysregulated emotions and hypersexuality or inappropriate sexual behavior in the context of couple relationships. This brings us to the relevance of interpersonal context to ER .…”
Section: Attachment and Its Legacy: Emotion Dysregulation And Hypersementioning
confidence: 95%
“…Indeed, both attachment anxiety and avoidances are associated with greater dissatisfaction with sexual interactions [21,22,23], and more negative affect concerning sexual experiences [15,24,25]. In their systematic review of the literature examining attachment and sexual functioning for this journal, Stefanou and McCabe [4] concluded that across studies that focused on a variety of satisfaction and functioning measures, attachment insecurity (avoidance and anxiety) was consistently associated with decreased reports of global evaluations of sexual satisfaction across relationship types (e.g., dating, married).…”
Section: Attachment and Sexual Satisfactionmentioning
confidence: 99%